A Comparative Clinical Study to Evaluvate the Efficacy of Vasadrakshadi Kashaya and Nayopayam Kashaya in Tamaka Shwasa w.s.r to Bronchial Asthma (AYUSHDHARA, 2025)
Tamaka Shwasa is a Pranavahasrotoroga. Any deviation from the normal physiology of respiration can be considered as Shwasaroga. The word Tamaka denotes darkness. The disease is termed Tamka Shwasa since it aggravates during Durdina/cloudy days and on adopting Kapaha and Vata aggravating food and regimens. Various etiological factors including diet, regimens, certain external factors and some diseases when aggravates finally leads to Shwasaroga. All these etiological factors aggravate Vata and Kapha dosha. Aggravated Kapha dosa accumulates in Pranavahasrotas obstruction normal flow of Prana vayu, when Prana vayu tries to overcome this obstruction, it takes a Villoma gati and moves upward resulting in Shwasa which is manifested as symptoms like breathing difficulty. Acharya Charaka has clearly mentioned the importance of Nidana parivarjana along with Shodhana and Shamana chikitsa with special importance to Vatahara, Brmhana and Shamana chikitsa. The present comparative study was done to evaluate the efficacy of Vasadrakshadi Kashaya and Nayopayam Kashaya in managing Tamaka Shwasa. It was observed that Vasadrakshadi Kashaya proved more effective in reducing Kasa in Tamak Shwasa patients, both Kashyas are effective but Nayopayam Kashya is more effective than Vasadrakshadi kashaya in managing Tamaka Shwasa.